Mobile Applications in the Care of Children and Teenagers in Oncological Treatment - Knob, Paula A.; Larentis, Andrêsa V.; Barbosa, Débora N. F.; Silva, Carla R. da; Barbosa, Jorge L. V. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
Cancer is the disease that most affects children and young people around the world. The treatment is long and ineffective when detected late. The technologies of mobile computing can be used to develop applications to assist patients during the cancer treatment. This article presents a systematic mapping of literature to identify articles that apply mobile applications to assist patients in cancer treatments, in order to show an overview of the literature, identifying gaps and research opportunities. The systematic mapping study was conducted in six databases including papers from January 2008 to December 2018. The initial search resulted in 41,888 papers, of which 31 were selected after applying the filter criteria. The main results obtained are: (1) most papers (61,29%) reported solutions based on native mobile applications; (2) majority (67,74%) focused on monitoring symptoms and side effects of cancer treatment; (3) most papers (61,29%) aimed physical benefits; (4) only two papers (6,45%) provided applications to leukemia patients; (5) four papers (12,9%) focused on palliative care; and (6) most papers (83,87%) conducted an experiment with oncological patients. The results corroborate with the need for mobile applications to help individuals in monitoring, psychological support, and information regarding about the disease, as well as evidence of research opportunities in palliative and supportive care.